2021
DOI: 10.3390/min11070785
|View full text |Cite
|
Sign up to set email alerts
|

Phosphorus-Rich Ash from Poultry Manure Combustion in a Fluidized Bed Reactor

Abstract: The aim of this study was to examine the physico-chemical and phase characteristics of ash obtained in the process of the combustion of Polish poultry manure in a laboratory reactor with a bubbling fluidized bed. Three experiments, differing in the grain size and morphology of the raw material, the method of its dosing and the type of fluidized bed, were carried out. The contents of the main chemical components and trace elements in the obtained ash samples were determined using WDXRF, and the phase compositio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 29 publications
2
5
0
Order By: Relevance
“…EDS analysis revealed the presence of K and S in these areas, which could indicate K 2 SO 4 formation. The presence of K 2 SO 4 has been observed in previous studies with chicken manure [9,18,[36][37][38] and in sewage sludge [39]. Similar structures can be observed also for the samples extracted after 8 h. Thus, it can be assumed that K 2 SO 4 forms during thermal conversion of chicken manure and accumulates preferentially within cavities and over time, migrates through the cavities deeper into the particles.…”
Section: Bib Cross-sectionssupporting
confidence: 81%
See 1 more Smart Citation
“…EDS analysis revealed the presence of K and S in these areas, which could indicate K 2 SO 4 formation. The presence of K 2 SO 4 has been observed in previous studies with chicken manure [9,18,[36][37][38] and in sewage sludge [39]. Similar structures can be observed also for the samples extracted after 8 h. Thus, it can be assumed that K 2 SO 4 forms during thermal conversion of chicken manure and accumulates preferentially within cavities and over time, migrates through the cavities deeper into the particles.…”
Section: Bib Cross-sectionssupporting
confidence: 81%
“…The speciation of phosphorus plays a major role regarding plant availability [41][42][43]. The formation of an amorphous phosphoruscontaining phase could be interesting for the application of the used bed material as a fertilizer, because amorphous phosphorus showed a higher plant availability than crystalline phosphorus [10,37,44]. Alternatively, the formation of alkali-phosphates was found to increase the fertilization value of phosphorus-rich sewage sludge ash [45][46].…”
Section: (G) and (H)mentioning
confidence: 99%
“…130 Phosphorus was also later reported to be largely associated in amorphous form in ashes from combustion of chicken manure. 618 Another study also reported that, in gasification of poultry litter, phosphorus was found as stable phosphates in the cyclone ash and only traces of gaseous phosphorus species were detected using MBMS. 126 5.2.3.…”
Section: Energymentioning
confidence: 97%
“…Normally, XRD analysis is only performed on the final biomass residues, and does therefore not provide a lot of information on the transformation pathways, but it gives an indication of the fate of phosphorus in thermal conversion of biomass. In an attempt to investigate what crystalline phosphates are most commonly found in biomass residues, the reported phases detected in 384 samples, from 65 references (refs , , , , , , , , , , , , , , , , , , , , , , , , , , , , , , , , , , , , , , , , , ) were compiled in this work. The result of the compilation is shown in Figure .…”
Section: Transformation Of Phosphorus In Biomass Conversionmentioning
confidence: 99%
See 1 more Smart Citation